Natural capital accounting as a decision support tool for environmental management of a protected area in Madagascar - Tony A. Ramihangihajason; Jean-Louis Weber; Solofo Rakotondraompiana; Edmond Roger; Miadana H. Faramalala; Solofoarisoa Rakotoniaina (PLoS ONE, 2025)
Ecosystem change affects the availability of resources and services provided by nature. Ecosystem Natural capital accounting helps track these changes and supports better decision-making for managing the environment. This approach aims to assess changes in the stocks and flows of natural resources and the possibility to integrate them into economic and political decisions. The protected area of Mahavavy-Kinkony Complex, in North-Western of Madagascar, was chosen to implement this approach due to its many types of ecosystems as well as important reserves of threatened birds. In five years (2013–2018), we have observed a reduction in woodland cover (forest and mangrove) due to both regulated and illegal logging, linked to urban expansion and increasing of human pressure. This loss of woodland compromises not only biodiversity but also the capacity of ecosystems to provide ecosystem services. At the same time, the silting up of surface waters is compromising water quality and the health of aquatic ecosystems. In addition, the increase in agricultural land at the expense of forested areas raises concerns about the continuing degradation of natural ecosystems. All of these changes can be observed inside local socio-ecological landscape type. Each socio-ecological landscape type shows the potential variation in the production of ecosystem services.